(3CNHGQ GdhGaOjf ef GdQLGd ef Cgd Gdchag hGdHUQg Ydi eYGhjI Hf CHj SajGfs
(3ChdgG (B:s
(3MOK GdMSf Hf GdMSf Hf YGUe , bGd GMVQJ eLdS eYGhjI GHf CHj SajGf hYfOg cHQGA GdchaI hQDSGA GdbHGFd s
(3BNQgG (B:s
(3hgPG eG GfJgi EdjfG ef MOjK GdhGaOjf ef Ggd Gdchag hGdHUQg Ydi eYGhjg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B12 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(467) s
Keywords: (3GdJGQjNs